Development of the Hash Function Using Modified Skew Tent Map to Improve Blockchain Technology - Salih, Raghad Kadhim; Aubad, Ali A.; Yasin, Mohammed; Hamad, Hadi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Using SHA256 in the Blockchain system for security purposes, as it is important in linking blocks and preventing tampering efficiently and securely. In order to further confirm the security of SHA256 and protect it and increase its susceptibility to resist threats that it is exposed to in one way or another, its algorithm was developed by utilizing the modified skew tent map (MSTM). The developed SHA256 algorithm (D-SHA256) is distinguished by two essential features: less time and more enhanced security than its predecessor SHA256. This distinction arises from the strongly chaotic behavior and the highly randomness properties of the MSTM. Moreover, the proposed D-SHA256 algorithm consist of 32 rounds while preserving the randomness properties of the compression function by combining 48 hash constants and 48 words with the MSTM to obtain high randomness with less rounds. D-SHA256 guarantees that in the event of small changes that may occur in the input message leading to large changes in the output hash digest, while confirming the preservation of the properties of the cryptographic hash, containing collision resistance and ideal confusion and diffusion. The proposed algorithm was compared with SHA256 and other current hash algorithms, the results showed that D-SHA256 has increased collision resistance, higher output randomness, better cryptographic hashing properties, and lower execution time